Emerging Spintronic Materials and Functionalities - Guo, Lidan; Hu, Shunhua; Gu, Xianrong; Zhang, Rui; Wang, Kai; Yan, Wenjing; Sun, Xiangnan (Advanced Materials, 2023)
The explosive growth of the information era has put forward urgent requirements for ultra-high-speed and extremely efficient computations. In direct contrary to charge-based computations, spintronics aims to use spins as information carriers for data storage, transmission, and decoding, to help fully realize electronic device miniaturization and high integration for next-generation computing technologies. Currently, many novel spintronic materials have been developed with unique properties and multi-functionalities, including organic semiconductors (OSCs), organic-inorganic hybrid perovskites (OIHPs), and two-dimensional materials (2DMs). These materials are useful to fulfil the demand for developing diverse and advanced spintronic devices. Herein, we systematically reviewed these promising materials for advanced spintronic applications. Due to the distinct chemical and physical structures of OSCs, OIHPs, and 2DMs, their spintronic properties (spin transport and spin manipulation) were discussed separately. In addition, some multifunctionalities due to photoelectric and chiral-induced spin selectivity (CISS) were overviewed, including the spin-filter effect, spin-photovoltaics, spin-light emitting devices, and spin-transistor functions. Subsequently, we presented challenges and future perspectives of using these multifunctional materials for the development of advanced spintronics.
Keywords: chiral-induced spin selectivity; two-dimensional materials; multifunctional spintronic devices; organic semiconductors; organic-inorganic hybrid perovskites